Survey on Kuala Lumpur to Singapore High-Speed Rail (KL-SG HSR) Project among Pagoh Residents - Nasir, Nur Afifah; Mohd Asrah, Norhaidah (2021)
The Kuala Lumpur to Singapore high-speed rail (KL-SG HSR) project is the first HSR that will be built in Malaysia. This project aim is to facilitate the journey between Malaysia and Singapore. The total length of the KL-SG HSR project is 350 kilometers, it covers 335 kilometers in Malaysia and 15 kilometers in Singapore which can shorten the traveling time between Malaysia and Singapore within 90 minutes compared to four or five hours taken currently by road, seven hours by classic rail service or three hours by air transport. The issues about the HSR project started after the 14th general election when Tun Dr. Mahathir said that this project was not necessary and could be scrapped. After two weeks later, Tun Dr. Mahathir Mohamad clarified that this HSR project was not being scrapped but merely postponed for a few years. Because of this situation, it is crucial to get public opinion and reaction regarding this issue. The study focuses on the public's opinion toward the HSR project among Pagoh residents. Pagoh is selected because, in the planning of this HSR project, there will be a station to be developed in Pagoh. This study determines the awareness of Pagoh residents on the HSR project, identifies the most important source they get the information about the HSR project, and studies their opinion about the implementation of HSR project according to the general scope of HSR, economy, and the future expectation of the project. The data collected using questionnaires distributed online and by face to face. The methods used to analyze the survey data are the Pareto analysis, Chi-Squared, Cramer's V, and Mann-Whitney U test. 263 respondents participated in this study and the results found that the majority of the respondents are aware of the HSR project, but they still have lack knowledge and information about the project. Television is the most important source for the respondents getting information on the HSR project and most of the respondents have positive responses toward the HSR project.